Pengaruh Lama Penyimpanan Terhadap Mutu Ikan Cakalang Asap (Katsuwonus pelamis) - Azis Husen; Ruslan A. Daeng (Sangia Publishing, 2018)
Moked fish is one of the processed products that can be used as raw material for processing together with the use of combinations and chemicals from fuel combustion. This research is to obtain the best time in the process of curing skipjack (Katsowonus pelamis) so that it can produce smoked fish meat with good quality. The purpose of this study was to determine how long the storing capacity of smoked skipjack meat and its quality. This study uses microbiological and organoleptic testing, namely to find out the color, taste, texture, aroma, smell by using statistical analysis. Based on the results of the organoleptic test analysis on smoked skipjack meat on color, taste, aroma, appearance, and texture of the five treatments, the smoked fish products can still be accepted by the panelists while for the 2nd and 3rd day, fish meat which is stored seen from the quality and quality and taste of smoked fish has been contaminated with fungi and bacteria on the day 4,5,6,7,8, and the 9th can not be consumed anymore, the temperature used for smoked smoked fish is 80-110 oC whereas storage in 4oC freerer and storage of smoked fish for 9 days. Microbiological testing parameters with the results of testing the Total Plate Number (ALT) for samples of smoked skipjack with three analyzes get the first sample with a small value of 31,508 while the second sample with a value of 32,905 and the third one is 35,801 so the small battery is the first sample.